2004
DOI: 10.3748/wjg.v10.i1.147
|View full text |Cite
|
Sign up to set email alerts
|

Do there exist synergistic antitumor effects by coexpression of herpes simplex virus thymidine kinase with cytokine genes on human gastric cancer cell line SGC7901?

Abstract: AIM:To evaluate the synergistic antitumor effects of herpes simplex virus thymidine kinase (HSV-TK) together with tumor necrosis factor alpha (TNF-α) or interleukin-2 (IL-2) gene expression on gastric cancer cell line SGC7901. METHODS:Recombinant vectors pL(TT)SN and pL(TI)SN, which express TK-IRES-TNF-α and TK-IRES-IL-2 genes separately, as well as the control plasmids pL(TK)SN and pLXSN were employed to transfect PA317 cells respectively to generate the viruses that can stably express the objective genes thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…The bystander effect is the primary driving force of the suicide gene therapy strategy (36,37). The results of the present study demonstrated that GCV+5-FC was not only able to kill the transfected cells but was additionally able to kill neighboring untransfected cells.…”
supporting
confidence: 51%
“…The bystander effect is the primary driving force of the suicide gene therapy strategy (36,37). The results of the present study demonstrated that GCV+5-FC was not only able to kill the transfected cells but was additionally able to kill neighboring untransfected cells.…”
supporting
confidence: 51%
“…In studies of Tsuji et al [ 176 ], replication-competent oncolytic HSV was constructed as a vector to deliver TSP-1 to a gastric cancer microenvironment, and this enhanced antitumor efficacy in vitro and in vivo via direct antitumor and antiangiogenic mechanisms. Moreover, in gastric tumor cell line SGC7901, the synergistic antitumor effect of herpes virus thymidine kinase (HSV-TK) with TNF-α and IL-2 gene expression was evaluated, but with no significant effect [ 177 ]. On the other hand, other studies on mice model showed a therapeutic effect of HSV-TK expression [ 178 ], so further studies are needed in this matter.…”
Section: Oncolytic Viruses In Gastric Cancermentioning
confidence: 99%
“…IRES-based multicistronic vectors containing the combination of suicidal gene and immunomodulating cytokine have also been described. Such combinations do not lead to a synergistic enhancement of the antitumor effect in vitro; however, the direct immunomodulatory effect has not been evaluated [94]. Multicistronic vectors have also been used to inhibit tumor lymphangiogenesis and angiogenesis.…”
Section: Multicistronic Vectors For Cancer Therapymentioning
confidence: 99%